(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd GdEfSGf Ydi SGFQ GdMjhGf CeG HYO adeG cGf cJGH TeS GdYdhe eajOkG ai GddZI ZGjI GdEaGOI dcf cGf eMJhjkG Ydi PcQ edhc GdYQH s
(3BNQgG (B:s
(3BNQ GdehLhO efgG bhdg (B: (3S GdeheSI GdaGLQI ef GdfSGA hheO Gdjhe hGddjdI GTJO MQgeG hjhe heO hdjdI heOI hCheV GdQLd UGMHg CTGQ s
(3GdfSNI HgG MhGTs
(3HCWQGagG WeSs
(3HMhGTjgG JYdjbGJs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B86s
Keywords: (3GddZIs